Isolation of a gene encoding a cellulolytic enzyme from swamp buffalo rumen metagenomes and its cloning and expression in escherichia coli - Cheema, Tanzeem Akbar; Jirajaroenrat, Kanya; Sirinarumitr, Theerapol; Rakshit, Sudip K. (My University, 2012)
Ruminants are capable of hydrolyzing lignocellulosic residues to absorbable sugars by virtue of the microbial communities residing in their rumen. However, large sections of such microbial communities are not yet culturable using conventional laboratory techniques. Therefore in the present study, the metagenomic DNA of swamp buffalo (Bubalus bubalis) rumen contents was explored using culture-independent techniques. The consensus regions of glycosyl hydrolase 5 (GH5) family of cellulases were used as primers for PCR amplification. A full-length metagenomic cellulase gene, Umcel5B29, with a complete open reading frame (ORF) of 1611bp was identified. The similarity search analysis revealed that Umcel5B29 is closely related to the cellulases (73% to 98% similarity) of ruminal unculturable microorganisms, indicating its phylogenetic origin. Further analysis indicated that Umcel5B29 does not contain a carbohydrate binding module (CBM). Subsequently, Umcel5B29 was overexpressed in Escherichia coli. The recombinant enzyme worked optimally at pH 5.5 and 45C, a condition similar to the buffalo's rumen. However, the enzyme retained more than 70% of its maximal activity after incubation at pH 4-7 and more than 50% maximal activity after incubation at 30-60°C for 30min. These characteristics render Umcel5B29 as a potential candidate for the bio-stoning process of denim. © 2012 Taylor and Francis Group, LLC.
Keywords: Bio-stoning; Buffalo rumen; Cellulase; Metagenomic; Microorganism; Unculturable